Tunable surface boundary conditions in strain gradient crystal plasticity model. (June 2020) - Yuan, Sibo; Duchêne, Laurent; Keller, Clément; Hug, Eric; Habraken, Anne-Marie
Highlights: A strain gradient crystal plasticity law models Ni single crystal. External surface state is featured by its dislocation mobility. Internal behavior is affected by the surface state. Capabilities of 3 numerical methods to model the phenomena of surface permeability. Abstract: The behavior of dislocations in the neighborhood of a metallurgical interface or a free surface can be totally different depending on the boundary conditions. Dislocations cease to move and accumulate around impermeable interfaces, such as grain boundaries or hard (i.e. coated or oxidized) external surfaces. On the contrary, dislocations annihilate on free surfaces, as supported by the image force concept. However the behavior of dislocations depends on the true surface permeability, which falls between these two idealized cases. In this paper, two different numerical methods are applied to model the intermediate surface behaviors: the virtual image geometrically necessary dislocation approach and the generalized elastic foundation approach while a strain gradient crystal plasticity constitutive law simulates the response of a Ni single crystal. It is demonstrated that a uniform dislocation density field on the surface can only be obtained by a variant of the generalized elastic foundation approach. Graphical abstract: Image, graphical abstract